2007
DOI: 10.2119/2006-00070.lim
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Neural Stem Cell Markers NG2 and L1 in Human Angiomyolipoma: Are Angiomyolipomas Neoplasms of Stem Cells?

Abstract: Angiomyolipomas are benign tumors of the kidney which express phenotypes of smooth muscle, fat, and melanocytes. These tumors appear with increased frequency in the autosomal dominant disorder tuberous sclerosis and are the leading cause of morbidity in adults with tuberous sclerosis. While benign, these tumors are capable of provoking life threatening hemorrhage and replacement of the kidney parenchyma, resulting in renal failure. The histogenesis of these tumors is currently unclear, although currently, we b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Tumors originating from different tissue microenvironments are exposed to different vascular beds. The pre-existing vasculature in various tissues would provide an uneven opportunity for tumor angiogenesis, growth, invasion, and possibly drug responses [28, 29]. In this present study, we provide compelling evidence to demonstrate that tumors implanted in highly vascularized WAT and BAT tissues exhibit accelerated tumor angiogenesis and growth.…”
Section: Introductionmentioning
confidence: 52%
“…Tumors originating from different tissue microenvironments are exposed to different vascular beds. The pre-existing vasculature in various tissues would provide an uneven opportunity for tumor angiogenesis, growth, invasion, and possibly drug responses [28, 29]. In this present study, we provide compelling evidence to demonstrate that tumors implanted in highly vascularized WAT and BAT tissues exhibit accelerated tumor angiogenesis and growth.…”
Section: Introductionmentioning
confidence: 52%
“…One theory was proposed that angiomyolipoma may originate from a pluripotent cell derived from the neural crest that undergoes epithelial to mesenchymal transition to give rise to diverse structures including peripheral nervous system, melanocytes, facial structures, and some endocrine cells [27]. Angiomyolipoma also expresses other neural crest markers, including NG2 and L1, consistent with this hypothesis [28]. Based on the immunophenotypic profiles of the lesions and their own findings, Barnes et al [26] made a conjecture about pathogenesis of lymphangioleiomyomatosis and angiomyolipoma that the loss of TSC2 gene in neural crest epithelial cells could potentially promote epithelial to mesenchymal transition, resulting in the invasion and migration of the mutant cells to distant sites such as the lung, kidney, and axial lymphatics and tumor generation, finally.…”
Section: Discussionmentioning
confidence: 71%
“…Evidence for the non-host cell theory remains elusive (1,2). Recent studies on angiolipomas, a PEC-cell-associated group of tumors, showed positive neural stem cell markers for NG2 and L1, suggesting these cells (PECs) may originate from defective differentiating precursor stem cells (8). We believe a large LAM series study on NG2 and L1 antibodies would enlighten us on the histogenesis of the defective differentiating precursor stem cells.…”
Section: Discussionmentioning
confidence: 84%